2013
DOI: 10.1007/s00266-013-0202-5
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic Net in Rhytidoplasty: An Efficient and Safe Method for Preventing Hematoma in 405 Consecutive Patients

Abstract: The hemostatic net is an efficient and safe method for preventing early hematomas in rhytidoplasties. LEVEL OF EVIDENCE III This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 27 publications
0
43
0
1
Order By: Relevance
“…En 2004, Auervald comunicó haber obtenido buenos resultados en la prevención de hematomas en ritidectomía cuando colocaba una red hemostática de transfixión entre el SMAS y la piel (27). En nuestra experiencia, la sutura en red para hemostasia prolonga el tiempo quirúrgico, ya que se necesitan un notable número de suturas separadas entre 0,8 a 1 cm para cubrir toda el área intervenida.…”
Section: Discussionunclassified
“…En 2004, Auervald comunicó haber obtenido buenos resultados en la prevención de hematomas en ritidectomía cuando colocaba una red hemostática de transfixión entre el SMAS y la piel (27). En nuestra experiencia, la sutura en red para hemostasia prolonga el tiempo quirúrgico, ya que se necesitan un notable número de suturas separadas entre 0,8 a 1 cm para cubrir toda el área intervenida.…”
Section: Discussionunclassified
“…40 Minimizing the risk of hematoma formation has been a goal of facial cosmetic surgeons for decades. [41][42][43][44][45][46] The use of fibrin glue in facelift surgery has been studied for decades, and a recent review found data to support that fibrin glue does decrease the risk of hematoma. 43 The utilization of drains has similarly been studied for decades, and there is evidence to support drains decrease the risk of seroma formation.…”
Section: Faceliftmentioning
confidence: 99%
“…42,46 Postoperative hematoma following face lift surgery is such a serious concern, that more aggressive techniques such as the hemostatic net have been proposed. 41 Lastly, a very rare but dramatic complication follow facelift is pyoderma gangrenosum, an idiopathic inflammatory disease beginning with painful skin nodules that progress to ulcerations frequently in areas of trauma or surgery. 47…”
Section: Faceliftmentioning
confidence: 99%
“…Remaining identified studies addressed various other adjunctive measures, but in our view presented too few studies and/ or insufficient strength of evidence upon which to form an opinion as to their safety and effectiveness. This group included adjunctive measures directed at hematoma prevention (perioperative atenolol, 43 percutaneous quilting sutures, 44 and PRP 45 ) and those aimed at improving the longevity (GalaFlex 46 ) or cosmetic outcome (Liposuction, 47 barbed threads 48 ) of conventional facelift techniques.…”
Section: Other Adjunctsmentioning
confidence: 99%